Exploring Learners' Degree of Autonomy in the 21ST Century at Islamic Boarding School - Edy Waloyo; Ahmad Rifai; Siti Aisyah (UICELL, 2020)
Covid-19 pandemic forces learners to study away from the teacher. Islamic Boarding school learners do not study and do other activities at the school since they are home. Consequently, they need to build autonomy in learning all subjects and English since they have a different kind of teacher guidance in this learning mode. This research aims at exploring learners' degree of autonomy at the Islamic Boarding School in Kuningan City. This study is a qualitative study that used an online questionnaire and interviews to collect the data. Eighty learners fulfilled the questionnaire, and six learners and two English teachers were involved in the interview. Findings show that (1) Islamic Boarding school learners' degree of autonomy is reactive autonomy. It is because of their need for teachers' guidance to learn English is high. They are good at setting goals for their learning, while their ability to monitor and evaluate the learning process is considered low since most of them are neutral to these activities. (2) Learners' autonomous activities are done both in the classroom and beyond the classroom during learning at home.